Field evaluation of G10, a celery (Apium graveolens)-based topical repellent, against mosquitoes (Diptera: Culicidae) in Chiang Mai province, northern Thailand - Tuetun B. (2014)
The potential of G10, a celery (Apium graveolens)-based topical product, as a repellent against natural mosquito populations was evaluated in comparison to commercial (Insect Block 28) and standard (25% DEET) repellents in Chiang Mai province, northern Thailand. These repellent products afforded encouragingly excellent personal protection against a broad range of mosquito species belonging to various genera, including Aedes, Anopheles, Armigeres, Culex, and Mansonia. No mosquito bite was observed on the volunteers treated with G10 and Insect Block 28 throughout the field study, whereas two species, i.e., six A. barbirostris and two A. subalbatus, came to bite or land on 25% DEET-treated volunteers. Thus, it can be concluded that while G10 and Insect Block 28 exhibited similarly powerful repellent activities with complete (100%) protection, 25% DEET was effective in minimizing bites with 99.68% protection. G10 formula was also studied for physical properties and biological stability after being kept under two conditions; a heating and cooling cycle, and varying temperature and time storage. Most samples of stored G10 not only demonstrated a similarity in appearance and physical properties, but also provided comparable repellency to that of the fresh preparation. These findings encourage commercial development of G10 formula as an alternative to conventional synthetic repellents. © 2008 Springer-Verlag.